2021
DOI: 10.1037/tmb0000006
|View full text |Cite
|
Sign up to set email alerts
|

Non-driving-related tasks during level 3 automated driving phases–measuring what users will be likely to do.

Abstract: After activation of a Society of Automotive Engineers (SAE) Level 3 automated driving function (SAE International, 2021), the function takes over the driving task and the human user may engage in other, non-driving-related tasks (NDRTs). Meanwhile, the user needs to remain receptive to requests by the function because s/he needs to reengage in the driving task, when the function approaches a system limit and requests the user to take over. Hence, the effects of NDRT engagement on driver state and takeover beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…During automated driving, participants were instructed to perform an NDRT. As Shi & Frey (2021) indicated that participants primarily wanted to engage in reading, the task consisted of reading aloud a text that scrolled automatically on the side tablet. The text was an excerpt of the story of Tom Sawyer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During automated driving, participants were instructed to perform an NDRT. As Shi & Frey (2021) indicated that participants primarily wanted to engage in reading, the task consisted of reading aloud a text that scrolled automatically on the side tablet. The text was an excerpt of the story of Tom Sawyer.…”
Section: Methodsmentioning
confidence: 99%
“…In Level 3 automation, drivers may be on-the-loop if they supervise the road or out-the-loop if they are engaged in non-driving activities. Potential drivers of autonomous vehicles have been shown to want to perform new activities that require attentional resources such as reading, writing messages, eating, drinking, browsing the internet, or making phone calls (Pfleging et al 2016;Shi & Frey, 2021). Drivers can thus be expected to engage in non-driving activities that may divert their attention from the road (Naujoks et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Participants are instructed to engage in playing Tetris, reading a text and typing a summary of it, and watching a documentary film. These tasks are chosen because they are natural activities and likely to be performed when users have the choice [2,13]. Since these activities are applied in an experimental setting with instructions, they will be referred to as tasks in the following.…”
Section: Non-driving Related Tasksmentioning
confidence: 99%